Studies on the Phyllosticta Leaf Spot of Ginger - Premanathan T (Department of Plant Pathology, College of Horticulture, 1981)
Laboratory and field experiments of “The studies on the Phyllosticta leaf spot of ginger” were conducted at the College of Horticulture Campus, Vellanikkara during 1979-1981.